Longterm results after surgical thrombectomy and simultaneous stenting for symptomatic iliofemoral venous thrombosis - Hölper, Peter; Kotelis, Drosos; Attigah, Nicolas; Hyhlik-Dürr, Alexander; Böckler, Dittmar (European journal of vascular and endovascular surgery, 2010)
Objectives - To evaluate the longterm outcome of venous thrombectomy and simultaneous stenting in patients with acute, symptomatic iliofemoral deep venous thrombosis (DVT). - Methods - Between January 1996 and December 2007, a total of 45 patients underwent venous thrombectomy at our institution. Thrombectomy results were classified by intraoperative phlebography as: TYPE I=complete, TYPE II=partial, TYPE III=complete with stenosis other than thrombus, TYPE IV=permanent occlusion. TYPEs I and IV were excluded from this analysis because no endovascular repair was performed. 25 patients underwent a venous hybrid operation comprising balloon-catheter thrombectomy, thrombolysis and stenting of residual stensosis. Three TYPE 2 and 22 TYPE 3 lesions were diagnosed. Three patients died during follow-up from causes unrelated to their treatment. Three were lost to follow-up. Hence, 19 patients were examined. A retrospective, non comparative single-centre study was performed. - Results - Median follow-up was 68 months (range 3-129). Primary and secondary patency rates were 74% (14/19) and 84% (16/19), respectively. Re-thrombosis occurred within seven days of operation in 26% (5/19). Procedure related mortality was zero. There was no case of late re-thrombosis. Four patients showed post-thrombotic sequelae (CEAP: C1, 2 or 3s). No leg ulcer developed in any patient. - Conclusion - Venous thrombectomy with simultaneous stenting results in excellent longterm results in selected patients with symptomatic iliofemoral venous thrombosis.